2020
DOI: 10.1186/s12881-020-01057-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis on phenotype and genetic basis of Chinese Fanconi anemia patients: dismal outcomes call for nationwide studies

Abstract: Background: Fanconi anemia (FA) is the most common inherited bone marrow failure (BMF) syndrome with 22 related genes identified. The ALDH2 rs671variant has been proved related to accelerate the progression of BMF in FA patients. The phenotype and genetic basis of Chinese FA patients have not been investigated yet. Methods: We analyzed the 22 FA-related genes of 63 BMF patients suspected to be FA. Clinical manifestations, morphological and cytogenetic feathers, ALDH2 genotypes, treatment, and outcomes of the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…FANCA was the most frequently mutated gene (60.2%) in our study as reported in other populations (60%–80%)2 20 36(online supplemental table S3, figure 2). In the 82 patients with FANCA pathogenic variants, 96 pathogenic variants were identified, out of which 32 were novel.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…FANCA was the most frequently mutated gene (60.2%) in our study as reported in other populations (60%–80%)2 20 36(online supplemental table S3, figure 2). In the 82 patients with FANCA pathogenic variants, 96 pathogenic variants were identified, out of which 32 were novel.…”
Section: Resultssupporting
confidence: 83%
“…Seven of these 12 patients showed defective FANCD2-Ub (58.3%), and subsequent pathogenic variant analysis confirmed them to be FA cases. Defects in the downstream FA pathway genes, which do not affect FANCD2-Ub, are very rare (2%–6 %)4 20 in patients with FA, and we also found the downstream pathogenic variants in only ~2.2% of the Indian patients. Therefore, FANCD2-Ub analysis may be used as a reliable test for the diagnosis of FA.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Our sensors provide a toolkit that may help to improve our understanding of the potential roles of FA in various cellular processes. Some recent research examined Fanconi anemia patients and found that people holding the ALDH2 dominant-negative variant (ALDH2*2) had the tendency of accelerated progression of bone marrow failure (BMF) 48 , 49 . Study on Fancd2 , Aldh2 and Adh5 knockout mice have indicated the effect of increased endogenous formaldehyde in the process 4 , 5 .…”
Section: Discussionmentioning
confidence: 99%